PERAN MEDIA MASSA TERKAIT VAKSIN BOOSTER COVID-19 UNTUK IBU HAMIL - Susi Artuti Erda Dewi; Sartika; Maal Abrar (LPPM STISIP Persada Bunda, 2022)
This study aims to find out how the role of the mass media related to the Covid-19 booster vaccine for pregnant women. Mass media is a means of communication in delivering messages, as a communication tool to spread news to the wider community. By using various communication tools such as radio, newspapers, TV, movies, etc. For this reason, the mass media plays a very important role in spreading accurate news regarding the Covid-19 booster vaccine, especially for pregnant women. This study uses qualitative research methods and data collection techniques by studying literature and sources from books, journals, websites and newspapers that are relevant to the topics discussed in this study. The results of this study are that through mass media the wider community, especially pregnant women, can easily access official information submitted by the government regarding the Covid-19 booster vaccine and make it easier for the government to convey information to the public that the Covid-19 booster vaccine for pregnant women is safe. referring to the Circular regarding the covid-19 vaccination for pregnant women and the adjustment of screening in the implementation of the covid-19 vaccination, besides that, the covid-19 booster vaccine for pregnant women has also been recommended by the National Immunization Expert Advisory Committee.